211k views
1 vote
Determine all values of x that make the expression true. work in the space provided.

Determine all values of x that make the expression true. work in the space provided-example-1
User Anurupr
by
6.6k points

1 Answer

5 votes

The equation is given as shown below:


(2)/(x-3)=(x+4)/(x)

Step 1

Apply fraction cross multiply, defined as:


\begin{gathered} If \\ (a)/(b)=(c)/(d) \\ \text{then} \\ a\cdot d=b\cdot c \end{gathered}

Thus, we have:


\Rightarrow2x=(x-3)(x+4)

Step 2

Expand the right-hand side of the equation using the FOIL method given to be:


(a+b)(c+d)=ac+ad+bc+bd

Thus, we have:


(x-3)(x+4)=x^2+4x-3x-12=x^2+x-12

Therefore, the expression becomes:


2x=x^2+x-12

Step 3

Write out the equation in the standard form of a quadratic equation given to be:


ax^2+bx+c=0

Hence, we have:


\begin{gathered} x^2+x-2x-12=0 \\ x^2-x-12=0 \end{gathered}

Step 4

Solve using the quadratic formula given to be:


x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}

Given


\begin{gathered} a=1 \\ b=-1 \\ c=-12 \end{gathered}

Hence, we have:


\begin{gathered} x=\frac{-(-1)\pm\sqrt[]{(-1)^2-(4*1*\lbrack-12\rbrack)}}{2*1}=\frac{1\pm\sqrt[]{1+48}}{2}=\frac{1\pm\sqrt[]{49}}{2} \\ x=(1\pm7)/(2) \end{gathered}

Therefore, the values of x can be:


\begin{gathered} x=(1+7)/(2)=(8)/(2)=4 \\ or \\ x=(1-7)/(2)=(-6)/(2)=-3 \end{gathered}

Therefore, the possible solutions to the equation are:


x=4,x=-3

Step 5

Check for undefined points. This we can do by equating the denominator of the equation to zero.

Therefore, the undefined points are at:


\begin{gathered} x-3=0 \\ \therefore \\ x=3 \end{gathered}

or


x=0

ANSWER

Combining the solution and the undefined points, given that none of the solutions are at the undefined points, the solution to the expression is given to be:


x=4,x=-3

User Jvoll
by
6.2k points